Insuring the Missing Middle: The Structural Roadmap to Universal Health Coverage in India - Agastya Bhandari (International Journal of Social Science Research and Review, 2026)
India has committed to Universal Health Coverage by 2033, yet roughly 40% of its population — the "missing middle," too affluent for public safety nets but unable to afford private care — remains effectively uninsured, and household out-of-pocket expenditure stands at ~43% of health spending, more than double the global average and rising. This report reconstructs the affordability lens by measuring affordability in terms of household savings rather than income. Healthcare, which appears low-cost in absolute terms, proves unaffordable once measured against a household's savings - a lens that captures how one-time hospitalization can wipe out life-time savings. A single major procedure such as a CABG can erase a lifetime of savings for over 60% of households. It further projects that demographic ageing, the rising and earlier onset of non-communicable disease, and persistent double-digit medical inflation will push health spending from ~3% of GDP today toward 4.5–8% by 2047, mirroring the trajectory the United States travelled from ~7% to ~18% over five decades. The report locates the core obstacle in a pervasive trust deficit rooted in the sector's structural peculiarities — information asymmetry at underwriting, near-zero demand elasticity under third-party payment, provider control over most of the cost base, cohort-level pricing that results in adverse selection, and India-specific distortions such as treatment costs linked to room category. Against this diagnosis it advances five structural reforms: building the ABDM digital backbone to enable longitudinal, consent-based data for better underwriting; policy design using co-pay, deductibles, value-based insurance design, and narrow networks to cut premiums by an estimated 10–30%; group negotiation and standardised, evidence-based treatment protocols; integrated (payer-provider) care to shift from activity-based to outcome-based delivery; and unbundling real estate from healthcare services to lower the cost of treatment by ~25%. It concludes that a dedicated healthcare regulator is a structural necessity —healthcare providers operate under a fragmented and relatively loose oversight and will require coordinated efforts across states its status as a state subject — to enable transformational changes across all three axes of the WHO framework and make UHC by 2033 attainable.